Overview of the ECE measurements on EAST - Liu Yong; Zhao Hailin; Zhou Tianfu; Liu Xiang; Zhu Zeying; Han Xiang; Schmuck Stefan; Fessey John; Trimble Paul; Domier C.W.; Luhmann N.C.; Ti Ang; et al. (EPJ Web of Conferences, 2019)
Radiometer systems and a Michelson interferometer, have been operated routinely to detect the elec-tron cyclotron emission (ECE) from EAST plasmas for diagnosing the local electron temperature. A common quasi-optical antenna placed inside the vacuum vessel is employed to collect and focus the plasma emission, and the line of sight is along a radial chord. All of the systems are located in a diagnostic room where the plasma emission is transmitted by overmoded corrugated waveguide. In-situ absolute intensity calibration has been carried out for both the radiometer systems and the Michelson interferometer independently, to ensure that the ECE diagnostic provides an independent electron temperature measurement. In order to diagnose the small-amplitude electron temperature fluctuation, a correlation ECE (CECE) diagnostic has been designed and commissioned recently. The CECE diagnostic employs an independent antenna system which has improved poloidal resolution. A synthetic diagnostic is realized by using the simulation code SPECE to interpret the ECE data in plasmas with non-Maxwellian distribution, and preliminary results imply that the ECE data could be still useful as a localized measurement in plasmas with non-thermal electrons, such as the LHW-heated plasmas on EAST.